Erythrocytes enhance oxygen-carrying capacity through self-regulation - Ying Xu; Zhangjie Yu; Hanxuan Liu; Xiaohan Bian; Weiliang Tang (Frontiers in Physiology)
Once considered passive carriers of oxygen, erythrocytes are now understood to play active roles in regulating oxygen homeostasis and redox balance. This review examines the molecular mechanisms through which red blood cells adapt to hypoxic conditions, including nitric oxide (NO)-driven changes in membrane properties, βCys93-dependent S-nitrosylation, adenosine-induced activation of glycolysis, and the development of hypoxic memory via eENT1 degradation. Enzymes such as RBC eNOS, CYB5R3, and G6PD are essential for maintaining NO availability and redox balance by controlling redox state and NADPH synthesis. In addition to their role in gas transport, erythrocytes contribute to intercellular communication, retain organelle remnants under pathological conditions, and are being explored as platforms for drug delivery. Progress in nanotechnology and gene editing has expanded their clinical applications. These findings present erythrocytes as adaptable, multifunctional cells that connect cellular metabolism, vascular biology, and translational research.